Technical Analysis: An Asian Perspective - LIAW, Siqin (Institutional Knowledge at Singapore Management University, 2012)
Technical analysis, namely the moving average rule and the channel rule, is applied to the currency of an Asian managed floating exchange rate regime (USD/SGD) to see if opportunities for profitable trading exist. Instead of using only daily or monthly data, higher frequency time frames of 10, 15, 30 and 60 minutes are analyzed. Profitable strategies (if any) will be broken down and analyzed within smaller time frames to see if the profits are specifically in sample.